Generation of N‐Heterocycles via Tandem Reactions of N ′‐(2‐Alkynylbenzylidene)hydrazides. Issue 1 (23rd October 2015) - Qiu, Guanyinsheng; Wu, Jie
Abstract: As a powerful synthon, N ′‐(2‐alkynylbenzylidene)hydrazides have been utilized efficiently for the construction of N‐heterocycles. Since N ′‐(2‐alkynylbenzylidene)hydrazides can easily undergo intramolecular 6‐ endo cyclization promoted by silver triflate or electrophiles, the resulting isoquinolinium‐2‐yl amides can proceed through subsequent transformations including [3 + 2] cycloaddition, nucleophilic addition, and [3 + 3] cycloaddition. Several unexpected rearrangements via radical processes were observed in some cases, which afforded nitrogen‐containing heterocycles with molecular complexity. Reactive partners including internal alkynes, arynes, ketenimines, ketenes, allenoates, and activated alkenes reacted through [3 + 2] cycloaddition and subsequent aromatization, leading to diverse H ‐pyrazolo[5, 1‐ a ]isoquinolines with high efficiency. Nucleophilic addition to the in situ generated isoquinolinium‐2‐yl amide followed by aromatization also produced H ‐pyrazolo[5, 1‐ a ]isoquinoline derivatives when terminal alkynes, carbonyls, enamines, and activated methylene compounds were used as nucleophiles. Isoquinoline derivatives were obtained when indoles or phosphites were employed as nucleophiles in the reactions of N ′‐(2‐alkynylbenzylidene)hydrazides. A tandem 6‐ endo cyclization and [3 + 3] cycloaddition of cyclopropane‐1, 1‐dicarboxylates with N ′‐(2‐alkynylbenzylidene)hydrazides was observed as well. Small libraries of these compounds were constructed. Biological evaluation suggested that some compounds showed promising activities for inhibition of CDC25B, TC‐PTP, HCT‐116, and PTP1B. Abstract : As a powerful synthon, N ′‐(2‐alkynylbenzylidene)hydrazides have been utilized efficiently for the construction of N‐heterocycles. Since N ′‐(2‐alkynylbenzylidene)hydrazides can easily undergo intramolecular 6‐ endo cyclization promoted by silver triflate or electrophiles, the resulting isoquinolinium‐2‐yl amides are amenable to subsequent transformations including [3 + 2] and [3 + 3] cycloadditions and nucleophilic addition.